The Lie as An Indicator of Social Maladjustment of Young People - Janina Florczykiewicz; Lesław Pytka (Nicolaus Copernicus University in Toruń, 2020)
The aim of the study was to compare views and attitudes towards lies held by Polish teenagers who were properly socialized and socially maladjusted (179 people). The diagnostic survey method and the questionnaire technique were used. It has been established that socially adapted youth better recognize lies, more often use altruistic and manipulative lies, more often lies to parents and teachers. Also, being lied to more often, they react with breaking contact with the liar and experience disappointment and anger; moreover, in the situation of being caught lying, they experience shame more often. In turn, socially maladjusted young people use destructive lies that aim to hurt someone. It was also found that the use of a lie, views on the admissibility of a lie and the tendency to justify it are independent of social adaptation.